School resources, peer inputs, and student outcomes in adult education - J. Lucas Tilley (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
This paper studies a large-scale educational expansion to evaluate whether shocks to school inputs have an impact on the academic achievement of adult education students. I analyze the spillover effects of a Swedish policy that temporarily doubled enrollment in adult education, thus putting considerable strain on school inputs. Since the policy targeted individuals age 25 and over, my analysis focuses on individuals under age 25 to mitigate concerns that changes in student composition drive my findings. First, I establish that students in regions subject to larger enrollment shocks experienced stronger negative shocks to peer quality and school resources such as teacher credentials and perpupil expenditure. Then, I show that the stronger negative shocks to peer quality and school resources coincided with larger increases in course dropout. Taken together, the two sets of results suggest a causal link between school inputs and course dropout.
Keywords: I20; I21; I28; 330; adult education; educational expansion; per-pupil spending; school resources; student achievement; teacher credentials